1912
DOI: 10.1007/bf02622217
|View full text |Cite
|
Sign up to set email alerts
|

Blutzerfall, Galle und Urobilin

Abstract: Aus der II. medicinischen Klinik der Kgl. CharitY. Blutzerfall, Galle und Urobilin. Zur Frage der Gallenfarbstoffbildung aus Blur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1915
1915
1949
1949

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It was not until Tarchanoff (2739), working 503 with bile fistula animals, demonstrated that the introduction of pure hemoglobin into the circulation led to increased excretion of bile pigment by the liver, that the ability of the animal body to convert hemoglobin into bilirubin became generally accepted. The latter has been confirmed by a number of workers (371,372,998,2605), and Whipple and his collaborators (cf. Section 8.1.)…”
Section: Breakdown Of Hemoglobin and Myohemoglobin To Dipyrrolic Compoundsmentioning
confidence: 70%
See 1 more Smart Citation
“…It was not until Tarchanoff (2739), working 503 with bile fistula animals, demonstrated that the introduction of pure hemoglobin into the circulation led to increased excretion of bile pigment by the liver, that the ability of the animal body to convert hemoglobin into bilirubin became generally accepted. The latter has been confirmed by a number of workers (371,372,998,2605), and Whipple and his collaborators (cf. Section 8.1.)…”
Section: Breakdown Of Hemoglobin and Myohemoglobin To Dipyrrolic Compoundsmentioning
confidence: 70%
“…Almost all hypotheses ignored obvious physiological and histological hints as to the chain of reactions, and envisaged the transformation almost solely in terms of chemical steps which could be carried out at that time in the test tube. As a result of the isolation of hematin and hematoporphyrin the steps were considered to be hemoglobin, hematin, hematojlorphyrin, bilirubin (371,372,697,1859). While Brugsch's school (370-372) claimed that they had observed increases in bilirubin excretion after injection of hematin, and in this received some support from Van de Velde (286Jf) ,* these findings have not been confirmed by Gitter and Heilmeyer (1007) or by Duesberg (639).…”
Section: Earlier Theories Of the Mechanismmentioning
confidence: 99%